AN ANALYSIS ON TRADERS’ INCOME AND ECONOMIC MOTIVATION TOWARD THEIR BEHAVIOR IN PAYING ZAKAT COMMERCIAL - Novia, Nely; Noor, Iswan; Ekawaty, Marlina (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
This study intends to determine and analyze the influence of economics factor: income (X1) as well as economic motivation (X2) towardMadurese traders? behavior in paying zakat commercial (Y). To analyze the data, multinomial logit (Mlogit) model was employed. The result of this study indicated, as simultaneously,income (X1)and economic motivation (X2) greatly influences Madurese traders? behavior in paying zakat commercial (Y). And partially, Madurese traders? behaviorin payingzakat commercial (Y) was affected by income(X1) and economic motivation (X2) as well.